The effect of chlorpyrifos on protein content and acid DNase activity in the mussel, Mytilus galloprovincialis. Issue 4 (3rd July 2016) - Kovačić, I.; Medić, N.
Abstract: We evaluated the effects of short-term exposure to an organophosphate pesticide chlorpyrifos on the digestive gland and gills of the mussel Mytilus galloprovincialis . We studied metabolic activity by quantifying protein content and physiological function responses using acid DNase activity. The increase in protein content was observed in both the target tissues of mussels exposed to 0.03 μg/L chlorpyrifos when compared with control mussels. The pattern of acid DNase activity in digestive gland and gills indicated a tissue-specific response, although the lowest concentration of chlorpyrifos caused changes in acid DNase activity in both tissues. In the digestive gland, the increase of acid DNase activity was observed in mussel exposed to 0.03 μg/L chlorpyrifos, followed by decrease up to 100 μg/L chlorpyrifos. Enzyme activity in the gills showed a dose response effect. The results support the use of acid DNase activity in the digestive gland as a sensitive response to an environmentally relevant range of pesticide concentrations. It may also indicate an effect on mussel physiological status.